1989
DOI: 10.1080/09540128908253032
|View full text |Cite
|
Sign up to set email alerts
|

Sex worker, client sex behaviour and condom use in Harare, Zimbabwe

Abstract: One-hundred sex workers and 100 clients were interviewed at a bar/disco complex in Harare, Zimbabwe in 1989. Sociodemographic characteristics of sex workers and clients were examined. Almost a third of sex workers and nearly 90% of clients had engaged in commercial sex over 5 or more years. Sex workers reported that they worked an average of 4.6 nights a week, averaged 2.2 clients a night and charged a mean of Z$8.7 per session and Z$19.8 per night. Clients reported that they averaged 7.4 visits a month to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 7 publications
2
34
1
4
Order By: Relevance
“…10 The only published study which shows relatively high client levels was one done of sex workers in bars in Harare in 1989, where Wilson et al reported average rates of 10.1 clients per week. 11 We have been unable to find any other published reports of sex workers with a client turnover of four per day as found in the Nairobi Prostitutes Study. 5 We should underline the fact that the townships in our study are on the outskirts of Nairobi; the furthest, Ngong Town, is hardly 30 minutes from the centre of Nairobi by public transport.…”
Section: Discussionmentioning
confidence: 75%
“…10 The only published study which shows relatively high client levels was one done of sex workers in bars in Harare in 1989, where Wilson et al reported average rates of 10.1 clients per week. 11 We have been unable to find any other published reports of sex workers with a client turnover of four per day as found in the Nairobi Prostitutes Study. 5 We should underline the fact that the townships in our study are on the outskirts of Nairobi; the furthest, Ngong Town, is hardly 30 minutes from the centre of Nairobi by public transport.…”
Section: Discussionmentioning
confidence: 75%
“…32 En otro estudio de Wilson y colaboradores, entre 100 trabajadoras sexuales y 100 clientes en Harare, Zimbabwe, los autores encontraron que las trabajadoras sexuales laboraban 4.6 noches por semana en promedio, con 2.2 clientes por noche. 17 En un estudio realizado entre 62 trabajadoras de 22 burdeles en Colombia, 79% tenían 2-3 clientes por noche en una "buena" noche. 33 En un estudio en Bali, Indonesia, con 80 trabajadoras sexuales que trabajaban con clientes que eran turistas y 100 clientes de este tipo, las trabajadoras reportaron un promedio de 3.3 clientes en la semana pasada.…”
Section: Frecuencia De Las Prácticas Sexuales Con Clientesunclassified
“…También fueron frecuentes la estimulación manual de los genitales de la trabajadora (81%) y de los del cliente (76%), y el beso (58%), cosa que no ocurre en las trabajadoras sexuales de la Ciudad de México. 17 En un estudio en Gambia, que duró 14 meses e incluyó zonas urbanas y semirrurales, los autores decidieron que no era necesario registrar las prácticas de las trabajadoras sexuales con sus clientes, ya que de la observación etnográfica concluyeron que casi siempre el servicio consistía en la penetración vaginal únicamente, sin estimulación manual ni otros tipos de penetración. 38 Entre la población estudiada por de Gallo y Alzate en Colombia, el servicio incluía sólo penetración vaginal; los clientes pedían (pero las trabajadoras sexuales dijeron no aceptar) servicios orales y anales.…”
Section: Prácticas Sexuales Profesionalesunclassified
See 2 more Smart Citations